ANALISIS IMPROVISASI JAZZ VOKAL SARAH VAUGHAN PADA LAGU "LULLABY OF BIRDLAND" - Wibowo, Annya Pharameshtrie (Jurnal Penelitian Musik, 2021)
The Purpose Of This Research is to know how Sarah Vaughan's jazz improvisation of vocal on the song "Lullaby Of Birdland". The object of this research is focused on improvisation in terms of the melody and harmony in Sarah Vaughan's singing. The Research Methodolody used in this research is descriptive qualitative research methodology. The instrument used was the researcher herself. This research was conducted from March 2020 to January 2021 at home, Jalan Sapta Taruna Raya RT 08 RW 10 Blok 23 No. 301, Komplek P.U., Lebak Bulus, South Jakarta. Data collection techniques used library research, audio research, "Lullaby Of Birdland" by Sarah Vaughan’s transcript, and interview. The data analysis technique was carried out by reading books related to the song “Lullaby Of Bridland”, listening, reviewing, and identifying every Sarah Vaughan’s jazz improvisation in it, then researching Sarah Vaughan's jazz vocal improvisations, and conducting interviews with the expert. To check the validity of the data, the researcher conducted triangulation. The Results shows that improvisation was carried out in the introduction (m. 1-4), then in the middle of the song with the accompaniment of the chorus A (m. 68-71) A '(m. 76-79) B (m. 83-87) A ”(m. 91-99), in this section she plays a trade four along with three instrumental players. And the last improvisation was on the coda (m. 116-120). Sarah Vaughan’s jazz improvisation consist major scale, melodic minor scale, major pentatonic scale, minor pentatonic scale, blues minor pentatonic scale, Ionian and Aeolian modes, then arpeggios, and major licks.